Beer fermentation performance and sugar uptake of Saccharomycopsis fibuligera–A novel option for low-alcohol beer - Methner, Yvonne; Magalhães, Frederico; Raihofer, Luis; Zarnkow, Martin; Jacob, Fritz; Hutzler, Mathias (Frontiers in Microbiology, 2022)
There is a growing trend for beers with novel flavor profiles, as consumers demand a more diversified product range. Such beers can be produced by using non-Saccharomyces yeasts. The yeast species Saccharomycopsis fibuligera is known to produce exceptionally pleasant plum and berry flavors during brewer’s wort fermentation while its mycelia growth is most likely a technological challenge in industrial-scale brewing. To better understand and optimize the physiological properties of this yeast species during the brewing process, maltose and maltotriose uptake activity trials were performed. These revealed the existence of active transmembrane transporters for maltose in addition to the known extracellular amylase system. Furthermore, a single cell isolate of S. fibuligera was cultured, which showed significantly less mycelial growth during propagation and fermentation compared to the mother culture and would therefore be much more suitable for application on an industrial scale due to its better flocculation and clarification properties. Genetic differences between the two cultures could not be detected in a (GTG)5 rep-PCR fingerprint and there was hardly any difference in the fermentation process, sugar utilization and flavor profiles of the beers. Accordingly, the characteristic plum and berry flavor could also be perceived by using the culture from the single cell isolate, which was complemented by a dried fruit flavor. A fermentation temperature of 20°C at an original gravity of 10 °P proved to be optimal for producing a low-alcohol beer at around 0.8% (v/v) by applying the S. fibuligera yeast culture from the single cell isolate.